The mechanism of decision-making in the U.S. foreign policy: between national and private interest - E. A. Bezrukov (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2015)
The article analyzes the main features of the mechanism of decision-making in the United States foreign policy. The author emphasizes that the determining factor influencing the behavior of the American state in the international arena is dependent on the specifics of the relations within American political leadership. As the balance of power within the American political elite can change drastically in a short period of time, U.S. foreign policy is inconsistent.